2017
DOI: 10.1016/j.jvs.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral inline replacement of infected aortofemoral graft limb with femoral vein

Abstract: This limited series demonstrates excellent graft patency with a low persistent infection rate. Thus, in patients with localized graft infection, partial excision with preservation of the proximal synthetic graft is an acceptable alternative when patient factors preclude complete graft excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Retrospective studies reported no re-infection after 2.5 years in 11 patients after interposition of unilateral silver coated grafts, 163 no re-infection after partial interposition with cryopreserved allografts in 10 patients after three years, 185 and a 9.5% re-infection rate after partial resection with autologous vein interposition in 20 patients after 72 months. 186 Limited resection of only infected material and reconstruction by obturator canal bypass (n ¼ 18) or part of a bifurcated graft (n ¼ 34) was also proposed with reinfection rates of 6% and 0%, respectively, and no amputation at 36 months. 187 Other series reported a 47% (n ¼ 7/ 15 patients) infection rate of the contralateral limb after 39 months, when partial resection of an aortobifemoral VGI and EAR was performed.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Retrospective studies reported no re-infection after 2.5 years in 11 patients after interposition of unilateral silver coated grafts, 163 no re-infection after partial interposition with cryopreserved allografts in 10 patients after three years, 185 and a 9.5% re-infection rate after partial resection with autologous vein interposition in 20 patients after 72 months. 186 Limited resection of only infected material and reconstruction by obturator canal bypass (n ¼ 18) or part of a bifurcated graft (n ¼ 34) was also proposed with reinfection rates of 6% and 0%, respectively, and no amputation at 36 months. 187 Other series reported a 47% (n ¼ 7/ 15 patients) infection rate of the contralateral limb after 39 months, when partial resection of an aortobifemoral VGI and EAR was performed.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…As expected, none of the studies were randomized control trials. The primary characteristics of clinical studies and covariates used in this meta-analysis are detailed online in (Supplementary, Appendix F) [7][8][9][10]17,18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…The mean number of patients across all studies was 50 (range: 2-220). There were 887 TR (84 %), and 165 PR (16%) with 6 studies (382 patients) combining TR (259 patients) and PR (123 patients) [ 9,29,32,34,38,40], 11 studies with solely TR (628 patients: 335 cryopreserved allografts, 259 autogenous veins, 23 standard polyesters/ PTFE, and 11 rifampicin-bonded polyesters) [7,8,10,28,30,31,33,35,39,41,42] and 4 studies with solely PR (42 patients: 23 autogenous veins, 11 silver-coated polyesters, and 8 standard polyesters/PTFE) [17,18,36,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations